1998
DOI: 10.1677/joe.0.1590519
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of prostaglandin production in intact fetal membranes by interleukin-1 and its receptor antagonist

Abstract: There is strong evidence for the involvement of inflammatory mediators such as interleukin (IL)-1 in the biochemical mechanisms of parturition. Therefore the effects of the IL-1 family (IL-1 (1 ng/ml), IL-1 (1 ng/ ml) and the IL-1 receptor antagonist (IL-1ra) (10 ng/ml)) on the regulation of prostaglandin synthesis in term human fetal membranes were investigated. It was found that, after 4 h of culture, IL-1 increased prostaglandin E 2 (PGE 2 ) output approximately twofold. This was associated with both a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 50 publications
0
37
0
Order By: Relevance
“…This is consistent with a relatively conservative 3-fold increase in neutrophil chemotactic potential of fetal membranes following labor [14], reinforcing the relative importance of macrophages in the labor process. Infiltration of macrophages may be a trigger for decidual activation due to their production of proinflammatory cytokines (e.g., tumor necrosis factor-a [TNF-a], interleukin [IL]-1b and IL6), and prostaglandins [15][16][17]. Moreover, decidual leucocytes may activate the tissues via paracrine actions of inflammatory mediators, resulting in amplification of leucocyte recruitment through upregulation of chemokines, and elevated production of labor-associated factors MMPs and prostaglandins, resulting in myometrial activation and fetal membrane rupture [16,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a relatively conservative 3-fold increase in neutrophil chemotactic potential of fetal membranes following labor [14], reinforcing the relative importance of macrophages in the labor process. Infiltration of macrophages may be a trigger for decidual activation due to their production of proinflammatory cytokines (e.g., tumor necrosis factor-a [TNF-a], interleukin [IL]-1b and IL6), and prostaglandins [15][16][17]. Moreover, decidual leucocytes may activate the tissues via paracrine actions of inflammatory mediators, resulting in amplification of leucocyte recruitment through upregulation of chemokines, and elevated production of labor-associated factors MMPs and prostaglandins, resulting in myometrial activation and fetal membrane rupture [16,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The severity of the fetal inflammatory response correlates with the levels of proinflammatory cytokines such as IL-1β, IL-6, and IL-8 in fetal plasma, with major perinatal morbidities and also with the severity of placental inflammation [14,24,26]. The cytokines subsequently activate matrix metalloproteinases (MMPs) and prostaglandin E 2 (PGE 2 ), which exert important effects on the degradation of extracellular matrix (ECM) and induce stimulation of preterm labor [4,5,1,21,32]. We have recently shown that the inflammatory response to intrauterine infection is more severe in preterm than in term fetuses.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we have already seen that IL-1ß stimulates cPLA2 synthesis and activity and PGE2 release by amnion WISH cells [72]. More precisely, Brown et al [108] showed that IL-1ß increased PGE2 output by intact fetal membranes about 2-fold, and COX-2 mRNA levels about 4-fold compared with controls; IL-1ß also significantly increased translocation of cPLA2 from the cytosol to the plasmic membrane.…”
Section: Production Of Free Arachidonic Acid and Prostaglandinsmentioning
confidence: 81%